Effectiveness of acute geriatric units in the real world: The case of short‐term mortality among seniors hospitalized for pneumonia. Issue 1 (11th April 2012) - Ding, Yew Yoong; Abisheganaden, John; Chong, Wai Fung; Heng, Bee Hoon; Lim, Tow Keang
<x xml:space="preserve">Abstract</x> Aim: We sought to compare the effectiveness of acute geriatric units with usual medical care in reducing short‐term mortality among seniors hospitalized for pneumonia in the real world. Methods: In a retrospective cohort study, we merged chart and administrative data of seniors aged 65 years and older admitted to acute geriatric units and other medical units for pneumonia at three hospitals over 1 year. The outcome was 30‐day mortality. Hierarchical logistic regression modeling was carried out to estimate the treatment effect of acute geriatric units for all seniors, those aged 80 years and older, and those with premorbid ambulation impairment, after adjusting for demographic and clinical characteristics, and accounting for clustering around hospitals. Results: Among 2721 seniors, 30‐day mortality was 25.5%. For those admitted to acute geriatric and other medical units, this was 24.2% and 25.8%, respectively. Using hierarchical logistic regression modeling, treatment in acute geriatric units was not associated with significant mortality reduction among all seniors (OR 0.72, 95% CI 0.52–1.00). However, significant mortality reduction was observed in the subgroups of those aged 80 years and older (OR 0.73, 95% CI 0.54–0.99), and with premorbid ambulation impairment (OR 0.65, 95% CI 0.46–0.93). Conclusions: Acute geriatric units reduced short‐term mortality among seniors hospitalized for pneumonia who were aged 80 years and older or had premorbid ambulation impairment. Further research is required to determine if this beneficial effect extends to seniors hospitalized for other acute medical disorders. Geriatr Gerontol Int 2013; 13: 55–62.